Sistema desponte na produção de figos verdes 'Roxo de Valinhos' - Campagnolo, Marcelo Angelo; Pio, Rafael; Dalastra, Idiana Marina [UNESP]; Chagas, Edvan Alves; Guimarães, Vandeir Francisco; Dalastra, Graciela Maiara (My University, 2010)
The objective of this research was to study the effect of the lopping system on the development and production of green figs 'Roxo de Valinhos'. The experiment using plants of four years of age, with spaced 3 × 2m, was conducted from July/2007 to March/2008 in Quatro Pontes, PR. The design was randomized blocks with four blocks, and the treatments arranged in a 2 × 5, taking as factors the number of productive branches (plants conducted with six or twelve branches) and the number of loppings (one, two, three or four, besides the control without lopping). In the lopping system, after the emission of the 16th leaf, the branch was blunted (apical bud removed), selecting two sprouting per productive branches. New lopping was accomplished later, always after the emission of sixth leaf. In each plot, consisting of the three plants, data were collected in the production cycles 2007/2008. The highest yield (2,208.87g planta-1) and estimated yield (3,681.19kg ha-1) observed of green figs were obtained when plants were conducted with twelve branches of production, effecting three loopings.
Lopping system in the production of 'Roxo de Valinhos' green fig
Keywords: Canopy structure; Ficus carica L.; Pruning